A multicenter micro-costing analysis of flexible cystoscopic procedures in Korea - Uiemo Je; Woong Kyu Han; Hee-Kyo Jeong; Hankil Lee; Kwang Suk Lee; Sung Ku Kang; Byeong-Ju Kwon; Sung-Uk Kuh (Investigative and Clinical Urology)
"Purpose: This study aims to develop and implement an economic evaluation using a micro-costing approach to provide a precise and transparent analysis of the direct costs of cystoscopic procedures in Korean hospitals. The study seeks to identify key cost components and evaluate whether current reimbursement rates accurately reflect these direct costs. Materials and Methods: Significant variations in cost items were identified across different studies. An economic evaluation was conducted using a micro-costing methodology for the cost analysis of cystoscopic procedures, developed through literature review, data collection from studies, and expert consultations. Results: Gangnam Severance Hospital (GSH) performed 2,188 cystoscopic procedures, including 1,847 cystoscopies and 341 JJ stent removals, with average costs of $100.8 and $110.6, respectively. At National Health Insurance Service Ilsan Hospital (NHIMC), 1,463 procedures were performed, including 1,167 cystoscopies and 296 JJ stent removals, with average costs of $119.2 and $125.3. Cystoscopy costs at GSH were driven by reprocessing ($45.8, 45.4%) and equipment ($33.1, 32.9%), while NHIMC’s were $52.5 (44.0%) for equipment and $48.7 (40.8%) for reprocessing. Both hospitals incurred financial losses, with NHIS (National Health Insurance Service) covering only about 71.7% and 60.6% of costs for cystoscopy, and 71.0% and 62.7% for JJ stent removal. Conclusions: The significant discrepancy between HIRA (Health Insurance Review & Assessment Service)’s estimated costs and those identified here suggests that current fees for cystoscopic procedures may be underestimated and require reassessment. Given the results, reevaluating these rates is essential to ensure fair compensation for healthcare providers and to deliver optimal patient care."